Assessing aerobic endurance in elite female cricket players - Boby, F. A.; Manisha B. (Scientific Journal of Sport and Performance, 2023)
To assess and compare the aerobic endurance levels of elite female cricket players from Bangladesh and India. This study`s participants were 50 elite female cricket players (ages 18-30 years), with 25 players from each country. They were all considered elite players based on their performance and experience in national and international cricket tournaments. To measure aerobic endurance fitness, the participants underwent a Yo-Yo Intermittent Recovery Test Level 1 (YYIRT1), which is widely used to measure an individual's maximal oxygen uptake (VO2max) and aerobic capacity. The data collected were analysed using descriptive statistics and inferential statistics. The test of Normality, mean, and standard deviation were calculated for each group, and a t-test was used to compare the mean scores of the two groups. A p-value of less than .05 is considered statistically significant. The data were analysed using the statistical software SPSS version 26. The study found that the Indian female cricket players had a significantly higher aerobic endurance fitness level than the Bangladeshi players. The mean VO2max of the Indian players was 46.76 ml/kg/min, while the Bangladeshi players' mean VO2max was 43.60 ml/kg/min. Additionally, the Indian players had a higher mean score in total distance covered in YYIRT1 (1233.6 m) than the Bangladeshi players (857.6). These differences were found to be statistically significant (p < .05). These findings suggest that there may be a difference in the training and preparation methods between the two countries, leading to a higher aerobic endurance fitness level among Indian players.